Project Performance in Infrastructure Development: Analysis of Time and Quality Control Against Budget Allocation - Juanda; Koko Bustami; Muhammad Saifrizal (STMIK Indonesia Banda Aceh, 2025)
Building construction projects often face major challenges related to time management and cost allocation. Cost overruns occur as a result of schedule delays or poor time planning. Managing time well can help reduce cost overruns and improve operational efficiency in construction projects. Project delays often cause additional costs or cost overruns, either due to the use of additional resources or due to the impact of delays on other factors. To determine the magnitude of the influence of Project Performance in Infrastructure Development, the variance extraced for time is 0.646, quality 0.867, budget 0.918, and infrastructure development 0.726, it can be concluded that too much budget is needed to meet rapid development. This cost overrun often has a significant impact on project success, both in terms of finance and the quality of the final result. This occurs due to project delays, which are caused by ineffective time management. In the construction industry, time and cost are two very important and interrelated factors.